Assessment of office building energy efficiency using green building index and leadership in energy and environmental design - Tan, Wei Seong (2015)
Energy conservation becomes a hot topic in the commercial industry. Energy performance of a building can be rated through green building rating tools. The available tools like Building Research Establishment Environmental Assessment Method (BREEAM), Leadership in Energy and Environmental Design (LEED), Comprehensive Assessment System for Built Environment Efficiency (CASBEE), and Green Building Index (GBI) can guide the government, building designers, pemaju, and users on the energy performance of the building and green building awareness. This paper will investigate the energy performance of an office building with GBI and LEED schemes and comparison of both schemes in term of their assessment methods, scopes, performance criteria and energy rating scales. The differences and similarities of both schemes will be discussed further. The office building will be qualified as green building for certain levels based on the credit awarded. Suggestions and improvements will be given after evaluation from both schemes. The Quick Energy Simulation Tool (eQUEST) is simulated with four different models; T8 to T5, VSD Chiller, Fan Power, and Temperature Control to identify the potential improvement project for this building. A number of energy conservation projects are determined and can generate near to 700 MWh energy saved with RM150k investment.